A Regression Model of Public Interest in COVID-19 Vaccination Ahead of MotoGP - Faiqotul Himmah, Elok; Riana, Riana (Jurnal Varian, 2024)
The lack of a threshold value for herd immunity against COVID-19 ahead of the MotoGP 2022 Event in the Mandalika Circuit Area, Central Lombok Regency is the reason for the author to conduct this research. The objectives of this research are 1) to make a mathematical model of the interest of the people of Central Lombok Regency in the Covid-19 vaccination in welcoming the 2022 MotoGP Event and 2) to determine the influence of MotoGP Event 2022 and other factors on the interest of the people of Central Lombok Regency in carrying out the COVID-19 vaccination. This research is a type of quantitative descriptive research. The independent variables in this study are the variables of ease of getting the Covid-19 vaccination (X1), the efficacy of the COVID-19 vaccination (X2), trust in the government (X3), and the 2022 MotoGP event (X4), while the dependent variable is the variable of interest in covid-19 vaccination (Y). To achieve the objectives of this study, the authors collected data through a questionnaire that was distributed to 332 respondents, they’re people who received the full vaccine aged 12-70 years. The questionnaire was tested for validity and reliability. Data must first be transformed into interval data using the Method of Successive Interval (MSI) then analyzed using multiple linear regression with classical assumptions including normality, multicolllinearity and heteroskedasticity. The results showed that the 2022 MotoGP event did not have a significant effect on the interest of the people of central Lombok Regency to take part in the COVID-19 vaccination. The biggest factor that influences is the factor of people's trust in the government.